Effects of Curcuma spp. on P-glycoprotein function - Ampasavate C. (2014)
The effects of Curcuma longa (khamin chan) and Curcuma sp. "khamin-oi" (khamin-oi), as well as isolated major curcuminoids on intestinal P-gp functions were evaluated in vitro. The accumulation of R123 in Caco-2 cells was increased and the R123 efflux ratios were significantly decreased by both Curcuma longa and Curcuma sp. "khamin-oi" extracts, indicating their roles on efflux transporters. The a-b transport of daunorubicin was increased by curcumin, demethoxycurcumin and bisdemethoxycurcumin while the b-a transport was significantly decreased by curcumin and demethoxycurcumin. However, calcein-AM uptake into the human P-gp overexpression cell line, LLC-GA5-COL300, was increased by curcumin and demethoxycurcumin in a concentration-dependent manner but not affected by bisdemethoxycurcumin. These results show that curcumin and demethoxycurcumin could inhibit P-gp but bisdemethoxycurcumin may modulate the function of other efflux transporters such as MRP. Taken together, the information may indicate the impact of Curcuma longa and Curcuma sp. "khamin-oi" on pharmacokinetics of orally administered drugs that are P-gp substrates. © 2009 Elsevier GmbH. All rights reserved.